A new framework for modeling decentralized low impact developments using Soil and Water Assessment Tool. (October 2017) - Her, Younggu; Jeong, Jaehak; Arnold, Jeffrey; Gosselink, Leila; Glick, Roger; Jaber, Fouad
Abstract: Assessing the performance of LID practices at a catchment scale is important in managing urban watersheds. Few modeling tools exist that are capable of explicitly representing the hydrological mechanisms of LIDs while considering the diverse land uses of urban watersheds. In this paper, we propose computational modules that simulate the hydrological processes of LIDs including green roof, rain garden, cistern, and porous pavement. The applicability of the modules was evaluated using plot scale experimental monitoring data. The effectiveness of LIDs was investigated in a highly urbanized watershed located in Austin, TX. Results indicate that the performance of LIDs is sensitive to LID configurations, application areas, and storm event characteristics, suggesting the need for studies on spatial optimization of LIDs and critical storm events to maximize the utility of LIDs. The LID modules offer a comprehensive modeling framework that explicitly simulates the water quantity processes of the LIDs considering landscape heterogeneity. Highlights: We propose modules for the explicit simulation of low impact development practices. LID practices simulated include green roof, rain garden, cistern, and porous pavement. New modules are integrated with Soil and Water Assessment Tool's sub-daily simulation. The integration enables to consider heterogeneous urban land uses in LID simulation. LID performance is responsive to storm event features as well as LID configuration.